Role of thyroid hormones in the implementation of adaptive reactions of the organism - Yu. A. Shatyr; N. O. Nazarov; R. I. Glushakov (Сибирский научный медицинский журнал, 2024)
The activity of thyroid hormones is one of the key elements in the regulation of the organism’s adaptive reactions. The article presents an analysis of thyroid hormones’s action mechanism as the organism’s response to environmental stress. The purpose of the study is to specify the role of iodothyronines in the formation of the organism adaptive reactions. Material and methods. The literature analysis was performed using the PubMed, SpringerLink, eLibrary, GoogleScholar databases for relevant publications for the period 2015–2023. Results and discussion. The development of both hypo- and hyperthyroidism negatively affects the functioning of a number of organs and systems of the organism. The consequences of changes in the level of thyroid hormones in the form of hypo- and hyperthyroidism for the adaptive capabilities of the organism are characterized, and the possibilities of correcting adaptive reactions by regulating their level are analyzed. Conclusions. To date, it has been proven that thyroid hormones are actively involved in the expression of more than 100 genes, maintaining redox balance, as well as in many metabolic reactions, which affects the adaptive potential of the organism. At the same time, the development of both hypo- and hyperthyroidism negatively affects the functioning of a number of organs and systems of the organism. Therefore, for a person to successfully adapt to stressful environmental factors, it is advisable to correct the content of iodothyronines in the organism. Actively used hormonal support, despite proven effectiveness, has nevertheless a number of limitations regarding the potential harm of such therapy, as a result of which approaches to correcting the content of iodothyronines are currently being analyzed, in particular, through the nutritional intake of a number of vitamins and microelements, as well as through dosed physical activity.